PERANAN PERAWAT GIGI DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK BERKEBUTUHAN KHUSUS (DISABLED CHILDREN) - I Gede Surya Kencana (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Dental health is one of the most important things for growing children. However, in Indonesia, not many parents are concerned about the dental health of children, especially in children with special needs. Children with special needs are children who have mental disorders are like autism, Down syndrome and cerebral palsy, "children with special needs have a higher risk of oral health problems. Dental nurse role in the maintenance of oral health in children with special needs is the oral health examination as early as possible, which made treatment plan should involve family or caregiver / person day-to-day help patients with activities, Doing modification of diet on children with special needs is to reducing diet carbohidrat and snack between meals and build method of oral health maintenance realistic for each of each child with special needs